Massive fetomaternal hemorrhage in a monochorionic-diamniotic twin pregnancy: a case report. (31st December 2023) - Liao, Shuying; Zhao, Jitong; Li, Tao; Yi, Tao; Lin, Xiaojuan; Bian, Ce; Ling, Chen
Abstract: Fetomaternal hemorrhage (FMH) result into severe, life-threatening fetal anemia and cause intrauterine death of the fetus. It is tough for an early diagnosis of FMH before pregnancy and few authors reported FMH in a twin pregnancy. Therefore, we reported a case of massive FMH. The patient felt a decrease in fetal movements at 33 +5 gestational weeks. Cardiotocography showed sinusoidal heart rate patterns in one fetus. The fetal hemoglobin level in maternal blood was 6.4% (normal range for single pregnancy, 0.0%–2.0%). Since the patient was diagnosed with fetal distress, cesarean section was performed and both babies delivered to receive neonatal treatment. Severe anemia was apparent in both neonates, based on red blood cell count, hemoglobin concentration, and hematocrit of 0.75 × 10 12 /L and 0.61 × 10 12 /L, 2.8 g/dL and 2.4 g/dL, and 10.0% and 8.4%, respectively. The neonates were admitted to the intensive care unit for prematurity care and presently are well. In our experience, an early diagnosis of FMH contributed to saving fetus. Obstetricians should highlight fetal movements counting to every patient. Once massive FMH occurs in monochorionic twins, both fetuses may develop severe anemia and require emergency intervention.